2020
DOI: 10.29054/apmc/2020.706
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Idiopathic Short Stature Children Presenting in OPD of Children Hospital, Faisalabad

Abstract: Methodology: A total of 300 children with 174 female, 126 males were studied, who came in OPD in Children Hospital Faisalabad for the evaluation of their short stature, excluding familial short stature and other causes of short stature (endocrinal, renal & other chronic illnesses). IgA, TTG & IgG antibodies were evaluated. These antibodies were measured by ELISA method and patients whose TTG antibodies were 10 times greater than normal were spared form duodenal biopsy, however patients having antibodies less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…The mean age of the study was 6.71±1.52 years. Approximately similar mean age (8.368 ± 2.387 years) was reported in a previous study conducted in Faisalabad on the prevalence of CD in idiopathic short stature [12]. Another study conducted in Iran also reported similar mean age [13].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The mean age of the study was 6.71±1.52 years. Approximately similar mean age (8.368 ± 2.387 years) was reported in a previous study conducted in Faisalabad on the prevalence of CD in idiopathic short stature [12]. Another study conducted in Iran also reported similar mean age [13].…”
Section: Discussionsupporting
confidence: 79%
“…This shows that short stature equally affects both genders in our population. But a previous study conducted in Pakistan shows female predominance [12].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, its prevalence in Scandinavia is 1.99 %. Recent studies have indicated that the prevalence of celiac disease in the United States is comparable to that in Western Europe ( Xia et al, 2020 ; Masood et al, 2020 ; Rostami et al, 2011 ). The four diagnostic criteria are malabsorption due to gluten consumption in wheat and barley, atrophy of the small intestinal mucosa, the improvement of clinical symptoms of malabsorption with the improvement of atrophic symptoms of the small intestine by cutting gluten-containing foods, and recurrence of clinical and histological symptoms after restarting gluten-containing foods ( Rubio-Tapia et al, 2013 ; Rozenberg et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%